Shape Reconstruction of Columnar Structure Defect. Issue 6 (2nd November 2022) - Zheng, Gangfeng; Dong, Hao; Li, Ze; Liu, Songfeng; Wu, Bin; He, Cunfu
ABSTRACT: In this study, a cylindrical test specimen with a 3D through-hole defect was processed, and the reflected echo data of the defect at different cross-sections were obtained by an ultrasonic testing detection system. On this basis, two data processing methods were designed to obtain two types of 3D reconstruction images of defects, and the reconstruction effects of two methods were compared using the real defects. In general, this study achieved a relatively accurate 3D reconstruction of through-hole defects at a low cost. Our methods provided lower cost than current state-of-the-art approaches.